CHOICE OF PRACTISES AND VARIANTS IN TRANINING OF A CIRCULAR ATTACKER - Fahrudin Mavrić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
One o f m ost impo rta nt function s in handball is play o f a circular pla yer of pivo t man. Data used for this wor k are partially from my o wn practical work, then, us in g of domest ic and f oreign ex pe rt s' literature as we ll as c onsultation s with fa mous domest ic and foreign top handball playe rs and co aches. Major part I have taken fr om my pe rs on al experience a s an active player but in recent tim e as a coach as well . The m a tter treated in this work is not o n ly a theore ti ca l consideration but i s also based mostl y upon so me pra ctical resu lts. Ha nd ball r el at ed lite ra ture domest ic and forein has advanced in a grea t way, meaning tha t many b ooks relating this matter have been writ ten in recent years . But al thoug h some books a boutn hadn ba ll pr actise have been wr itten, none o f them have an al yz ed individual pla y and training of a player for a certain task , in our ca se a "circular attack" Ma ny handbooks and tex ts published by ou r or f oreign e xpe rts explain o nly partially the play of a player at the lin e of 6 meters.